High frequency acoustic recording package data summary report PS06, January 30, 2009 -- April 30, 2009 - Margolina, Tetyana (Monterey, California. Naval Postgraduate School, 2011)
This summary continues a series of reports on the project, which seeks to assemble a census of marine mammal vocalizations in the high--frequency acoustic recording package (HARP, Wiggins and Hildebrand, 2007) data collected by the NPS Oceanography Department off Point Sur beginning in October 2006. The present report provides an initial summary of marine mammal vocalizations detected and identified in records from the sixth HARP deployment between February 1, 2009 and April 30, 2009. Data was acquired in the 10 Hz -- 100 kHz frequency band at a 200 kHz sampling frequency for 5 minutes during each 10 minute interval. Long-term spectral averages were created for three frequency bands (10 Hz--1000 Hz, 1 kHz-5 kHz, 5 kHz--100 kHz) and then scanned for marine mammal vocalizations. Detected calls of fin whales, humpback whales, as well as echolocations of sperm whales, beaked whales, and dolphins are presented as occurrence time diagrams. N00244-10-10031